Islamic Investment among Entrepreneurs: the Impact of Financial Literacy, Religiosity, and Risk Profile, With Technology as Moderating Variable - Hadie Bandarian Syah; Hulwati Hulwati; Aidil Novia; Trinitaria Marlis Putri (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
The low level of entrepreneurial participation in Islamic investment, despite the promising growth of the Islamic finance industry, serves as the main motivation for this study. This research aims to analyze the influence of financial literacy, religiosity, and risk profile on Islamic investment decisions, with technology as a moderating variable, among entrepreneurs in Padang City. A quantitative approach with descriptive and associative design was employed. Data were collected through questionnaires distributed to 100 Muslim entrepreneurs in Padang who owned at least one type of Islamic investment. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings reveal that financial literacy, religiosity, and risk profile have a significant positive effect on Islamic investment decisions. Technology was found to play a significant moderating role by strengthening the relationship between the independent variables and investment decisions. This study addresses a research gap by highlighting technology as a rarely discussed factor and positioning entrepreneurs as research objects based on the assumption that they possess greater investment capacity. Practically, the study provides insights for Islamic finance practitioners to continuously innovate and develop marketing strategies through technology. Academically, this research enriches the literature on Islamic finance by integrating it with social behavior and technological perspectives. Tingkat partisipasi kewirausahaan yang rendah dalam investasi syariah, meskipun industri keuangan syariah menunjukkan pertumbuhan yang menjanjikan, menjadi motivasi utama penelitian ini. Penelitian ini bertujuan untuk menganalisis pengaruh literasi keuangan, keagamaan, dan profil risiko terhadap keputusan investasi syariah, dengan teknologi sebagai variabel moderator, di kalangan wirausahawan di Kota Padang. Pendekatan kuantitatif dengan desain deskriptif dan asosiatif digunakan. Data dikumpulkan melalui kuesioner yang dibagikan kepada 100 wirausaha Muslim di Padang yang memiliki setidaknya satu jenis investasi syariah. Data dianalisis menggunakan Partial Least Squares Structural Equation Modeling (PLS-SEM) dengan perangkat lunak SmartPLS. Temuan menunjukkan bahwa literasi keuangan, keagamaan, dan profil risiko memiliki pengaruh positif yang signifikan terhadap keputusan investasi syariah. Teknologi ditemukan memainkan peran moderasi yang signifikan dengan memperkuat hubungan antara variabel independen dan keputusan investasi. Studi ini mengisi celah penelitian dengan menyoroti teknologi sebagai faktor yang jarang dibahas dan menempatkan wirausaha sebagai objek penelitian berdasarkan asumsi bahwa mereka memiliki kapasitas investasi yang lebih besar. Secara praktis, studi ini memberikan wawasan bagi praktisi keuangan Islam untuk terus berinovasi dan mengembangkan strategi pemasaran melalui teknologi. Secara akademis, penelitian ini memperkaya literatur keuangan Islam dengan mengintegrasikannya dengan perspektif perilaku sosial dan teknologi.